Telecoaching in Traumatology - Lemieux, R.; Masson, P.; Bellemare, C.; Martin, M.; Bisson, D.; Bernard, M.-È.; Fauteux, P.; Julien, C.; Lalonde-Filion, M.; Morier, C.; Morin-Guimond, A.; Patry, M-A; et al. (CMBES Proceedings, 2007)
No Abstract